2003
DOI: 10.1016/s0886-3350(03)00471-1
|View full text |Cite
|
Sign up to set email alerts
|

Oral pilocarpine for the treatment of keratoconjunctivitis sicca with central corneal irregularity

Abstract: A 31-year-old female physician with bilateral myopia had unilateral myopic laser in situ keratomileusis in the right eye. The patient was overcorrected with the initial treatment and had 2 subsequent hyperopic treatments, resulting in central corneal irregularity. During the course of treatment, the patient was diagnosed with Sjögren's syndrome with marked keratoconjunctivitis sicca. The patient had anisometropia, aniseikonia, and monocular diplopia and was unable to tolerate contact lenses. Oral pilocarpine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Of the total of 36 eyes, 19 eyes were placed in the BSCLs group. The study found that SiHy contact lenses were more While there is evidence of management success with soft contact lenses, there are various case series and cohort studies that report either complications from BSCLs in Sjøgren syndrome patients or a failure of soft lenses to provide adequate corneal protection [223,[253][254][255][256][257][258]. A cohort study of 69 consecutive microbial keratitis cases in various ocular surface diseases found 20 cases corresponding to 17 Sjøgren syndrome patients, nine of which were associated with soft contact lens use.…”
Section: Sjøgren Syndromementioning
confidence: 99%
“…Of the total of 36 eyes, 19 eyes were placed in the BSCLs group. The study found that SiHy contact lenses were more While there is evidence of management success with soft contact lenses, there are various case series and cohort studies that report either complications from BSCLs in Sjøgren syndrome patients or a failure of soft lenses to provide adequate corneal protection [223,[253][254][255][256][257][258]. A cohort study of 69 consecutive microbial keratitis cases in various ocular surface diseases found 20 cases corresponding to 17 Sjøgren syndrome patients, nine of which were associated with soft contact lens use.…”
Section: Sjøgren Syndromementioning
confidence: 99%